P094 COMPARING ORAL CORTICOSTEROIDS ≥30 MG/DAY USE AMONG PEDIATRIC AND ADULT PATIENTS WITH NEWLY DIAGNOSED CROHN'S DISEASE. (7th February 2019) - Hunter, Theresa; Naegeli, April; Komocsar, Wendy; Larkin, Amy; Schroeder, Krista; Zhang, Xiang; Stefani-Hunyady, Diana
Abstract: Abstract Body Background: Crohn's disease (CD) has a relapsing–remitting disease course. Sparing use of oral corticosteroids (CS) ≥30 mg/day, as mono or combination therapy, are generally reserved for rapid relief of symptoms and induction of remission to achieve optimal therapeutic response. This analysis aimed to compare patient profiles of adult and pediatric patients newly diagnosed with CD who use ≥30 mg/day CS in a real world setting. Methods: The Truven Marketscan commercial administrative claims database was used to explore the real-world utilization of ≥30mg/day CS among pediatric (children 2- 11 years old and adolescents 12-17 years old) and adult (≥18 years old) CD patients. Patients were identified based on first diagnosis of CD during 1/Jan/2013 -31/Dec/2015 and were included in the analysis if they had an additional CD diagnosis during the 1-year post-index period. Patients with pre-specified, common inflammatory comorbid conditions associated with high doses of oral CS were excluded. The final sample was subsequently stratified based on number of days (d) [0, 1-7, 8-30, 31-90, 91-180, 181-365] on ≥30mg/day oral CS during follow-up (1-year post diagnosis). Pre-index and post-index patient characteristics (demographics, medications, and health care resource use (HCRU)) are described. Results: A total of 8, 909 CD patients were included in this analysis consisting of 215 children (2-11 years old), 487 adolescents (12-17 years old), and 8, 207 adults (18+ years old). Demographic information such as age, gender, and geographic location for each subgroup is displayed in Table 1. Approximately, 30.23% of children and 33.06% of adolescents received corticosteroids ≥30mg/day during the post-index period, compared to only 13.59% of adults. In addition, 20.00% of children, 24.44% of adolescents, and 5.12% of adults received corticosteroids for more than 30 days during the 1-year post-index period. Among all subgroups, patients with ≥30 days of ≥30mg/day CS use were more likely to be prescribed biologics. HCRU (including gastroenterologist visits, emergency room visits, and inpatient visits) was higher for patients receiving ≥30mg/day of CS at least 1 day during the post-index period when compared to those not receiving ≥30mg/day of CS. HCRU was higher among the pediatric subgroups (children and adolescents) when compared to adults (Table 1). Conclusion: During a 1-year follow-up period, CD patients with a longer duration of ≥30mg/day CS use were more likely to be on a biologic and had increased HCRU. This analysis of real-world data suggests that there is a subset of newly diagnosed pediatric and adult patients with CD who may require longer use of higher doses of oral CS to achieve optimal therapeutic response. This analysis also suggests that pediatric CD patients are more likely to be prescribed corticosteroids and have higher HCRU when compared to the adult CD population.